MOBILISASI EMOSI MENUJU JURANG MOBOKRASI STUDI KASUS KAMPANYE #UnInstallTempo DI TWITTER - AMIR SODIKIN; JUNIARA JUWITA DWI UTARI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Political polarization on social media resulting from the presidential election contestation between Joko Widodo (Jokowi) and Prabowo Subianto continues to be felt. Supporters in both camps are still confined in a polarization situation which Lim (2017) calls algorithmic enclave. When Tempo Magazine published the cover of a magazine that was considered criticizing President Jokowi, his supporters on social media made a campaign to attack Tempo starting on September 15, 2019. The buzzers mobilized the masses by carrying the hashtag #UnInstallTempo. This emotional mobilization effectively dropped the Tempo app's rating on the Google Play Store from 4.8 (scale 1-5) to 1.1 within 3 days. Until now Tempo is still affected by this attack. This phenomenon further proves the danger of polarization which is compounded by the confirmation bias trap. Tempo attackers tend to seek confirmation of justification from the arguments of fellow supporters without wanting to hear arguments from Tempo and from other parties. In the end, the ways of democracy are threatened and if such conditions continue to gain a place in the eyes of citizens, policies and discourse in Indonesia will be determined by mobocracy.